Views from the University of Waterloo School of Optometry on Meeting with the Manpower Needs of the Future - Cullen, A.P. (Canadian Journal of Optometry, 2021)
The University of Waterloo continues to be the major source of optometrists for all provinces in Canada except Quebec and the student body is recruited from all provinces including Quebec. The pool of candidates for admittance remains high (300-400) and of an academic calibre that is increasing annually. Up to half the incoming students have B.Sc. or higher degrees and this year only two candidates with a single year of University have been offered positions, reflecting the trend in recent years. We continue to seek academically well-qualified students with broad interests and excellent interpersonal skills. With such a large pool it is possible to select these and attrition has been low with the loss or failure of only a handful of students. Unfortunately many well-qualified candidates are not admitted indicating that there will be no shortage of students for a third Canadian school.